Adaptive predictions of the euro/złoty currency exchange rate using state space wavelet networks and forecast combinations - Brdyś, Mieczysław A.; Brdyś, Marcin T.; Maciejewski, Sebastian M. (Zielona Góra: Uniwersytet Zielonogórski)
The paper considers the forecasting of the euro/Polish złoty (EUR/PLN) spot exchange rate by applying state space wavelet network and econometric forecast combination models. Both prediction methods are applied to produce one-trading-day-ahead forecasts of the EUR/PLN exchange rate. The paper presents the general state space wavelet network and forecast combination models as well as their underlying principles.
Keywords: currency exchange rate; artificial intelligence; state space wavelet network; Metropolis Monte Carlo; forecast combinations; data generating process